Acute kick-boxing exercise alters effective connectivity in the brain of females with methamphetamine dependencies. (16th February 2020) - Bu, Lingguo; Qi, Liping; Yan, Wu; Yan, Qian; Tang, Zekun; Li, Furong; Liu, Xin; Diao, Chunfeng; Li, Kefeng; Dong, Guijun
Abstract: Objective: Methamphetamine (METH) dependence, especially among women, is a serious global health problem. Kick-boxing exercise can be used to reduce cue-induced craving and develop a healthy lifestyle for female with METH dependencies. This study aimed to assess acute kick-boxing related changes in effective connectivity (EC) in the brain of females with METH dependencies by using functional near-infrared spectroscopy (fNIRS) signals. Methods: The fNIRS signals were continuously recorded from the left and right prefrontal cortices (LPFC/RPFC) and left and right motor cortices (LMC/RMC) of 30 female subjects with methamphetamine dependencies (METH group) and 30 age-matched controls (control group) during resting and kick-boxing exercise (training) periods. EC was calculated in the frequency range of 0.01–0.08 Hz. Results: In both resting and training state, the EC levels of METH group were significantly lower than the control group ( p  <  0.05). The EC levels of control group showed more significantly increased connection types than that of the METH group. Conclusion: Acute kick-boxing exercise altered EC in the brain of females with METH dependencies. Furthermore, the efficiency of the information flow between different brain regions in the control group was significantly higher than that in the METH group. This study provides a novel and portable assessment technique for METH rehabilitation in females on the basis of fNIRS signals.